An Efficient Heterogeneous Signcryption Scheme from Certificateless to Identity-based Cryptosystem - Niu Shufen; Li Zhenbin; Tian Miao; Wang Caifen; Jia Xiangdong (MATEC Web of Conferences, 2017)
The heterogeneous signcryption can not only realize the confidentiality and un-forgeability of the information transmission between different public key cryptography environments, but also reduce the communication cost. The proposed scheme uses bilin-ear pairings between certificateless cryptography and identity-based cryptography to construct a heterogeneous signcryption scheme. In addition, two cryptography systems use different secret master keys. Furthermore, the proposed scheme has the indistin-guishability against adaptive chosen ciphertext attacks and existential unforgeability against adaptive chosen-message attacks in the random oracle model. Through the data analysis, this scheme is more effective than other similar types of scheme.